The Influence of Successful Succession on the Progress of Family Business at PD Ayam Putra Kawalu - Amelia Nurisnaeni; Dwi Ramdani; Muhammad Rizqi Mardiansyah; Mira Nurfitriya; Azizah Fauziyah (UM Purwokerto Press, 2024)
A company's progress is the goal of its founding, and the transfer of power can influence one form of sustainability. Successful succession is essential to ensure the progress of the family business. This research examines the influence of successful sequence on the better progress of family business companies. The object of this research is a chicken trading company in the Tasikmalaya area, PD Ayam Putra Kawalu, which has branches. This research uses quantitative and descriptive-verification approaches to collect and analyze data. Quantitative data were obtained from questionnaire surveys and interviews with family business owners, including branches and successors. The sample is a family business with a branch company that has experienced succession. The results from the hypothesis show a positive relationship between successful sequence on the progress of the family business and producing leaders who will contribute to the progress of the family business. The findings of this research will contribute to understanding the challenges and opportunities for successful family business succession that will provide progress for the company.